Clinical epidemiological characterization of patients with non alcoholic fatty hepatic disease - Sixto Alain Dinza Cabreja; Juan Manuel Fernández Ávila; Maritza Dayami Galán Rodríguez; Anet Colas Ochoa; Vladimir Brice Abreu (Centro Provincial de Información de Ciencias Médicas, 2021)
Introduction: The non alcoholic fatty hepatic disease   is characterized by an increase of the lipids accumulation (triglycerides) in a macrovesicular way, in more than 5 % of the hepatic cells, associated or not with inflammation and/or hepatic fibrosis.  Objective: To characterize patients with non alcoholic fatty hepatic disease according to variables of interest for the study.  Method: A descriptive and cross-sectional study of 95 patients assisted in the Gastroenterology Service of Dr. Juan Bruno Zayas Alfonso Teaching General Hospital was carried out in Santiago de Cuba, from June to December, 2018. Among the variables figured: age, sex, risk factors, results of complementary exams, hepatic echography and clinical prognosis factors for the fibrosis.   Results: In the series there was a prevalence of the 35-44  and 45-54 age groups  (65.2 %, respectively), female sex,  obesity as main risk factor (50.5 %), transaminase glutamic piruvic-alanineaminotransferase (39.0 %) among the complementary exams with altered values and the moderate fatty liver as echographic finding (55.8 %), among others.   Conclusions: The non alcoholic fatty hepatic disease prevailed in patients between 35-54 years, where obesity constituted the most important risk factor; also, a greater number of patients presented high figures of transaminase glutamic piruvic-alanineaminotransferase and the echographic findings  revealed the primacy of the moderate steatosis. The presence of 4 or more prognosis factors constituted a risk for the development of hepatic fibrosis.